Efficacy of intravenous combined immunosuppression with plasmapheresis in adult patients with refractory primary focal segmental glomerulosclerosis. Issue 4 (9th May 2022) - Dirim, Ahmet Burak; Demir, Erol; Guller, Nurane; Safak, Seda; Artan, Ayse Serra; Oto, Ozgur Akin; Ozluk, Yasemin; Ozturk, Savas; Yazici, Halil; Kalayoglu‐Besisik, Sevgi; Turkmen, Aydin
Abstract: Background: Primary focal segmental glomerulosclerosis (FSGS) treatment is based on immunosuppressive therapies. Since refractory disease is common, alternative methods are emerging. One of these methods is plasmapheresis with intravenous cyclosporine and corticosteroids, and it could be an option in post‐transplant recurrent FSGS. We retrospectively investigated the efficacy of this combined treatment in adult patients with refractory primary FSGS. Methods: Seven refractory primary FSGS patients were included. Demographics, estimated glomerular filtration rates, serum albumin levels, urine protein/creatinine ratios, and previous treatments were evaluated. Also, complications and remission rates were assessed. Results: Median patient age was 23 years. Median duration of diagnosis was 2 years. Median number of plasmapheresis sessions was 14. Five of seven patients (71.4%, one complete, four partial remissions) were responders after the protocol. Changes in serum albumin levels and proteinuria after protocol were statistically significant ( P  = 0.018 and P  = 0.018, respectively). eGFR levels did not change statistically ( P  = 0.753). Median follow‐up duration after the treatment was 17 months. However, two patients experienced disease relapse (28.5%). End‐stage kidney disease was developed in two patients. Sustained remission rate was 42.8% during follow‐up (One complete and two partial remissions). Also, 42.8% of patients experienced catheter infections. Catheter‐associated thrombosis that required surgery was observed in a patient. Conclusions: Plasmapheresis combined with intravenous cyclosporine and corticosteroids could be an option in refractory primary FSGS. High response rates after this protocol were encouraging. However, the relapsing disease was observed after the cessation of apheresis. Also, complications of the protocol could limit the applicability.